THE POTENTIALS OF HISTORY STUDIES IN WAN YAHYA BIN WAN MOHD TAIB NOTE ABOUT THE 1914 MUSLIM PILGRIMAGE OF HAJJ MISSION - Mohd Kasri bin Saidon; Ishak Saat (Journal of Islamic, Social, Economics and Development, 2018)
This paper focuses on the personal record of a Kedah state chief named Dato 'Hj Wan Yahya bin Wan Mohd Taib on his journey to the holy land. This entry was the first in Kedah that wrote about the pilgrimage process and its whole experience. His writings are narrative but there are some aspects that touch on an analytical basis. His note is more complete and comprehensive than Abdullah Munshi's writings and is a rather detailed description of the journey of the pilgrimage to Mecca. Both of these writings are quite complete and comparable. Wan Yahya focuses more on the initial process of pilgrimage and later give his commentary on the journey to the holy land. The note that he Volume: 3 Issue: 11 [June, 2018] pp.1-12] Journal of Islamic, Social, Economics and Development eISSN: 0128-1755 Journal website: www.jised.com2 wrote brings potential for further research for historians, not just in Malaysia but this note is also worthy to Saudi Arabia. Many of the things that he touched have now become history and what is noted will be a more extensive research generation capital.